Ionic aggregate dissolution and conduction in a plasticized single-ion polymer conductor. (24th February 2015) - O'Reilly, Michael V.; Masser, Hanqing; King, Daniel R.; Painter, Paul C.; Colby, Ralph H.; Winey, Karen I.; Runt, James
Abstract: Poly(ethylene glycol) plasticizer is blended with a PEO-based single-ion conductor to lower the glass transition temperature of the ionomer and solvate the lithium counterions. With increasing plasticizer content at room temperature, FTIR spectra indicate that the fraction of ions in isolated ion pairs increases relative to those in ionic aggregates, and X-ray scattering data indicate that the ionic aggregates are further apart than expected by dilution alone. Together these data show that the average size of ionic aggregates decreases as PEG plasticizer is added. The dissolution of aggregates into ion pairs promotes ion conduction. Coupled with faster segmental dynamics and ion mobility from the depressed T g, the ionic conductivity of plasticized ionomers improved by two orders of magnitude at room temperature. Resolving the alpha relaxation of these ionomer blends reveals that the mechanism for ion transport is segmentally-assisted ion motion. Graphical abstract: Highlights: Lithium-conducting PEO ionomers were plasticized with PEG600. We observe the dissolution of ionic aggregates into ion pairs. Ionic conductivity was improved by two orders of magnitude. T g was reduced non-linearly with increasing plasticizer content.